Evaluation of Physically-Disabled Fighters’ Quality of Life at Rehabilitation Military Center in Al-Basra City (Medico Legal Update, 2020)
Objective(s): The aim of the study is to evaluate the physically- disabled fighters’ quality of life, and toidentify the relationship between the physically-disabled fighters’ quality of life and their socio-demographiccharacteristics.Method: A quasi-experimental design is carried throughout the present study at the Rehabilitation MilitaryCenter in Al-Basra City, Iraq,for the period of January 7th 2019 to October 31st 2019. Non-probability“purposive” sample of (27) physically disabled fighters’ is selected selected for the present study. Thequestionnaire is composed of two main parts (The Physically Disabled Socio-Demographic Characteristics,and Physically Disabled Fighters’ Quality of Life Evaluation Tool).The data are collected through theutilization of a developed questionnaire (Arabic version) and the use of structured interview techniquewith each physically disabled fighter as means of data collection. Test-retest reliability of instrumentwas determined through the use of Pearson correlation coefficient and content validity of the instrumentvalidity was determined through a panel of (18) experts. Data were analyzed through the use of descriptivestatistical data analysis approach of frequency, percentage, mean, mean of scores, total of scores, rangeand standard deviation and inferential statistical data analysis approach T-test, multiple linear regressions,person correlation coefficient,Chi-Square test, and analysis of variance (ANOVA).Results: The results of the study depict that the evaluation of physically-disabled fighters’ quality of lifeismoderate on the physical health domain,psychological health domain, and social relationship domainenvironment domain and spiritual health domain, and low on the level of independence domain; physicallydisabled fighters’ quality of life is significantly different relative to their age, residency, level of education,and chronic illness.Conclusion: The study concluded that the overall evaluation of physically-disabled fighters’ quality of lifeis moderate.